EMPOWERMENT OF INDONESIAN MILITARY RESERVE COMPONENT IN FACING THE PANDEMIC THREAT OF COVID-19 - Akhiyar Meideri; Syaiful Anwar (The Republic of Indonesia Defense University, 2021)
Reserve Components are National Resources that have been prepared to be mobilized to enlarge and strengthen the capabilities of the Main Components and Supporting Components. The theory used in this research is the theory of national defense, threat theory, and empowerment. The COVID-19 pandemic is a global health crisis problem that not only affecting the population health sector but also security. The decline in living conditions and people's welfare then also affects the security sector where there is an increase in the number of criminal acts that can threaten public security and order in Indonesia. Therefore, this study aims to find out how the government will empower the reserve components to help protect the country's sovereignty, maintain state security when the COVID-19 pandemic occurs and what steps have been taken by the Indonesian government. The result shows that the Indonesian Military Reserve Component including empowering Indonesian citizens that are implemented by participating and complying with various policies made by the government to reduce the spread of the virus, by implementing health protocols, online learning, enforcing lockdowns, and conducting social distancing. Meanwhile, the government also empowers the national facilities and infrastructure in controlling the COVID-19 virus, one of which is by improving the function of hospital services, cooperate with the mass media to spread information for the people. The government also use information technology to give health service for Indonesian to provide accurate information about COVID-19.